Multifunctional bioactive films based on carboxymethyl cellulose/sodium alginate incorporated with DES-lignin-stabilized ginger oil nanoemulsion and gallic acid for enhanced shelf-life of cherry tomatoes - Asad Mukhtar; Muhammad Abdur Rehman Shah; Haoxin Li; Xiaojie Yu; Albert Abugri; Allah Rakha; Rana Abdul Basit; Areej Munir; Li Chen; Hua Yang; Cunshan Zhou (Food Hydrocolloids, 2026)

Non-destructive honey adulteration fraud identification using hyperspectral imaging and deep learning - Muhammad Aqeel; Shahzad Hussain; Hammad Shahab; Khan Bahadar Khan; Kashif Munir (Food Control, 2026)

Bioactive organic and inorganic compounds in Latin American foods and plants: A review - Muhammad Abdurrahman Munir (Food and Humanity, 2026)

From commensal to pathobiont: The emergence of virulence-enhanced Escherichia coli in China's food-animal systems – insights with future implications - Nishant Shah; Asim Munir; Muhammad Shafiq; Muhammad Shoaib (Food Research International, 2026)

A hybrid approach for COVID-19 detection: Combining Wasserstein GAN with transfer learning - Sumera Rounaq; Shahid Munir Shah; Mahmoud Aljawarneh; Ghulam Muhammad (Next Research, 2026)

A Column Perfusion Study to Test Semi-Interpenetrating Polymer Embedded Biochar Based Slow-Release Fertilizers Efficiency in Mitigating Nutrients Leaching - Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. F. Al-Farraj; Munir Ahmad; Taieb Aouak; Hamed Ahmed Al-Swadi (Water, Air, & Soil Pollution, 2026)

Lornoxicam Loaded Transethosomal Gel: Formulation, Box-Behnken Optimization, Ex-Vivo and In-Vivo Characterization - Minahal Munir; Sarah Ahmad; Talha Jamshaid; Huma Hameed; Muhammad Zaman; Usama Jamshaid; Muhammad Jamshaid; Sara Khalid; Heba A. Gad (Journal of Pharmaceutical Innovation, 2026)

Corrigendum to “Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae” [South African Journal of Botany 196 (2026) 715–723] - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

A small-scale experimental prototype for exhaust heat-based mechanical energy harvesting in passenger vehicles, with extrapolation to heavy vehicles - Muhammad Bader Munir; Muhammad Waheed Ashraf; Najam ul Qadir; Sibghat Ullah; Allah Ditta (Next Research, 2026)

Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

Monitoring of insecticide resistance and associated fitness costs in diamondback moth, Plutella xylostella, (L.) (Lepidoptera: Plutellidae): Lesson from fields of Pakistan - Muhammad Shehzad; Muhammad Tariq; Muhammad Asif Aziz; Lu ZhaoZhi; Munir Ahmad (International Journal of Tropical Insect Science, 2026)

Redox homeostasis and trace metal regulation drive allantoin-induced tolerance against combined microplastic and cadmium stress in pea (Pisum sativum L.) - Anshra Murtaza; Muhammad Munir; Rizwan Rasheed; Muhammad Arslan Ashraf; Fakhar Abbas; Sarah Owdah Alomrani; Abdulrahman Alasmari; Shafaqat Ali; Sajjad Hassan Askari (Journal of Trace Elements in Medicine and Biology, 2026)

Dairy farm waste as a source of novel and globally disseminated multidrug-resistant Escherichia coli clones: A genomic and phylogeographic study - Muhammad Shoaib; Minjia Tang; Asim Munir; Muhammad Shafiq; Mashkoor Mohsin; Xuejing Zhang; Zhongyong Wu; Zhuolin He; Baocheng Hao; Shengyi Wang; Ruichao Li; Wanxia Pu (Journal of Hazardous Materials, 2026)

Characterization of Sugarcane Genotypes for Bioenergy Production: Exploiting In Vitro Mutagenesis to Ameliorate Energy-Related Traits - Shafquat Yasmeen; Sana Munir; Muhammad Abu Bakar Jaffar; Muhammad Tahir Khan; Imtiaz Ahmed Khan (Sugar Tech, 2026)

Machine learning and response surface modeling for predicting strength loss of alkali-activated materials exposed to aggressive environment - Munir Iqbal; Sohaib Nazar; Muhammad Hasham Kashif; Muhammad Ashraf; Haji Sami Ullah (Innovative Infrastructure Solutions, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Use selenium-doped TiO2 single-wall carbon nanotubes as promoter of biochemical indices in Solanum lycopersicum L. under bacterial wilt stress conditions - Asif Kamal; Akhtar Munir; Khizar Hayat Khan; Ulfat Ara; SK Safdar Hossain; Abdulrazak J. Otaru; Muhammad Tahir Amin; Hayat Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Deciphering the structural–functional dynamics of glucosyltransferases from novel Apilactobacillus isolates through in silico analysis - Hira Kiran; Munir A. Anwar; Waqar Ahmad; Iqra Jawad; Ayesha Siddiqa; Muhammad Imran; Moazur Rahman; Muhammad Saleem (Biologia, 2026)

Plant growth-promoting rhizobacteria (PGPR) producing ACC deaminase and exopolysaccharides enhance salt tolerance in wheat - Mahnoor Hayat; Rashida Parveen; Muhammad Shoib Nawaz; Muhammad Ahmad Rao; Ahmed Waqar; Rubab Zahra. Naqvi; Munir Ahmad Anwar; Zahir Ahmad Zahir; Muhammad Qasim; M Ahmad Dogar; Tadeo Sáez Sandino; Brajesh K. Singh; et al. (World Journal of Microbiology and Biotechnology, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Integrating Nanotechnology and Bioremediation for Efficient Heavy Metals Removal in Aquatic Ecosystems: A Comprehensive Review - Nadia Yasin; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Muhammad Asrar; Muhammad Mudassar Shahzad; Adan Naeem (Water, Air, & Soil Pollution, 2026)

Mineralogical characterization and rock physics parameter estimation in sandstone reservoir: A template-based approach and cross-plots analysis - Muhsan Ehsan; Muhammad Nofal Munir; Rujun Chen; Muhammad Ali; Kamal Abdelrahman; Ali Y. Kahal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

A freak-wave event-curation workflow for predicting mooring-line tensions and platform response of floating offshore wind turbines - A.K. Muhammad; Z. Nizamani; Aqeel Ahmed; Akihiko Nakayama; Mirza Munir Ahmed (Ocean Engineering, 2026)

Sustainable valorization of recycled polypropylene waste in concrete composites via compression casting: Integrating lifecycle, cost, and engineering assessments for plastic waste management - Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Yu-Fei Wu (Environmental Research, 2026)

Synthesis of Novel Bentonite Composites for Enhanced Remediation of Basic Fuchsin Dye - Ayesha Naseer; Ruba Munir; Gadah Albasher; Muhammad Husnain Manzoor; Murtaza Sayed; Faheem Abbas; Saima Noreen (Water, Air, & Soil Pollution, 2026)

Attenuating the Dual Injury of Deficit Irrigation and Salinity On Wheat Physiology and Productivity Via Amending Soil with Compost and Biochar - Ahmed R. Abd El-Tawwab; Khaled M. A. Ramadan; Basma R. Abdel-Moatamed; Shimaa A. Abd El-Mageed; Sallah A. Al Hashedi; Zafar Iqbal; Salim A. Ali; Muhammad Munir; Hani S. Saudy; Taia A. Abd El-Mageed (Journal of Crop Health, 2026)

Molecular detection of Toxoplasma gondii in Amblyomma gervaisi ticks infesting monitor lizards (Varanus bengalensis) - Muhammad Naeem; Muhammad Ammar Ameen; Hafiza Misbah Munir; Huma Fatima; Shakir Ullah; Hira Muqaddas; Kasim Sakran Abass; Adil Khan; Furhan Iqbal (Experimental and Applied Acarology, 2026)

Seasonal shifts in algal communities driven by environmental gradients in Kallar Kahar Lake, Pakistan - Mubashrah Munir; Rahmatullah Qureshi; Fahim Arshad; Asma Jabeen; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah; Muhammad Waheed (Limnology, 2026)

Validating the Efficiency of the AquaCrop Model Under Full and Deficit Irrigation Regimes to Simulate Future Climate Impacts on Wheat Crop - Shamim Ara Memon; Irfan Ahmed Shaikh; Mashooque Ali Talpur; Abdul Rahim Junejo; Munir Ahmed Mangrio; Nazar Gul; Zaheer Ahmed Khan; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2026)
Wheat yield and water demand are affected by the ongoing disturbance of climatic factors and greenhouse gases (GHG). As a result, the AquaCrop model's ability to anticipate climate change impacts on wheat harvests under full and deficit irrigation regimes in Sindh, Pakistan, was evaluated using wheat trials conducted between 2018 and 2020. However, for its validation, the results of the deficit irrigation treatment ITS 50 (50% controlled irrigation at the tillering stage) for both seasons were employed. The model efficiently estimated yield with a normalised root‐mean‐square error (NRMSE) of 13% and 17%, a Willmott's d ‐index of 98% and a Nash–Sutcliffe efficiency (NME) of 95% under full and deficit irrigation treatments, respectively. The simulation results revealed an adverse effect of climate change on the yield and water productivity of wheat. Over the century, the model predicted an increase of 6% to 7% in wheat yield under full (well‐watered) irrigation and a decrease of 10 to 12% in 25% reduced water applied depth (RAD) and 21% to 24% under 50% RAD scenarios for both representative concentration pathway RCPs (4.5 and 8.5). The overall wheat water productivity increased under a well‐watered irrigation regime by 16% in RCP8.5 compared with RCP4.5.

Decoding the cold: integrated secretome profiling reveals extracellular adaptation mechanisms in Glaciozyma antarctica - Shuhaila Mat-Sharani; Farahayu Khairuddin; Nik Yusnoraini Yusof; Norfarhan Mohd-Assaad; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nor Muhammad Mahadi; Nurdiana Nordin; Shazilah Kamaruddin (Extremophiles, 2026)

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Efficacy of Foliar-applied Chitosan Nanoparticles in Enhancing Drought Tolerance of Maize (Zea Mays L.) Through Morpho-Physiological and Biochemical Modulation - Ayesha Rukhsar; Rana Muhammad Waqas; Sarfraz Ahmed; Nian Lili; Momal Munir; Abdul Razzaq; Muhammad Arslan Asghar; Muhammad Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Retraction notice to “Highly antifouling polymer-nanoparticle-nanoparticle/polymer hybrid membranes” [Sci. Total Environ. 810 (2022) / 152228] - Vahid Vatanpour; Maryam Jouyandeh; Seyed Soroush Mousavi Khadem; Shadi Paziresh; Ahmad Dehqan; Mohammad Reza Ganjali; Hiresh Moradi; Somayeh Mirsadeghi; Alireza Badiei; Muhammad Tajammal Munir; Ahmad Mohaddespour; Navid Rabiee; et al. (Science of The Total Environment, 2026)

BAMPP: A novel Bayesian network enhanced by average marginal posterior probabilities to identify critical ground truth meteorological stations for drought monitoring - Rizwan Niaz; Saman Munir; Muhammad Ahmad Raza; Rifat Tur; Sadegh Partani; Ali Danandeh Mehr (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Novel Styrofoam-sludge biochar for Pb and Zn adsorption: Bioavailability and reduction in maize-cultivated contaminated soils - Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Ruilian Yu; Gongren Hu; Balal Yousaf; Sajid Ali; Muhammad Adnan; Cheng Liping; Xiangliang Pan; Ming Hung Wong (Journal of Cleaner Production, 2026)

Hyperbranched aromatic polyamide-modified nanofiltration membranes for improved water permeability and salt rejection - Muhammad Adnan Akram; Shengchao Zhao; Mengting Wang; Munir Hussain; Q. Jason Niu (Desalination, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Laccase purification and azo dye decolorization potential of Sparassis latifolia - Abdul Rehman Niazi; Tehreem Fatima; Aneeqa Ghafoor; Munir Ahmad; Muhammad Asad Ghafoor; Abdulaziz Bentalib; Muhammad Bilawal Junaid; Imran Haider (Natural Product Research, 2026)

pH-responsive MIL-101(Fe)/NiFe-LDH composite membranes for high-flux removal of cationic and anionic dyes in wastewater treatment - Shehriyar; Arslan Khurram; Abdul Jabbar; Muhammad Asim Khan; Wenhao Liu; Sadaf Mutahir; Akhtar Munir; Sameerah I. Al-Saeedi (Desalination, 2026)

Experimental Study of Local Scour Around Two Compound Piles in Tandem, Side-by-Side and Staggered Arrangements Under Steady Current - Muhammad Adnan; Ming Zhao; Helen Wu; Adnan Munir; Vatsal Dhamelia (Journal of Marine Science and Engineering, 2025)
Scour around two compound piles (CPs) in tandem, side-by-side (SBS), and staggered arrangements is investigated through experiments. Each CP has a larger diameter foundation, which is partially buried, and a smaller diameter top part with a diameter ratio of 0.5. The exposed height of the foundation is equal to its diameter. Experiments are conducted for gap ratios from 1 to 3. Due to the shadowing effect from the upstream CP, the downstream CP in the tandem arrangement has shallower scour depth and its most downstream point has deposition at an early stage. In the SBS arrangement, the scour does not have much difference from that of a single CP, but the inner side of each CP has a slightly deeper scour hole than the outer side of each CP and scour hole became independent at gap ratio of 3. In the staggered arrangement, the shadowing effect from the upstream CP was experienced by the downstream CP when G/D = 1, but not 1.5 and 3.

Retraction notice to “Development of reduced graphene oxide-supported novel hybrid nanomaterials (Bi2WO6@rGO and Cu-WO4@rGO) for green and efficient oxidative desulfurization of model fuel oil for environmental depollution” [Environ. Res., Part A, 212 (2022), 113160] - Aqsa Riaz; Muhammad Saeed; Mamoona Munir; Azeem Intisar; Sabah Haider; Shahzaib Tariq; Nazim Hussain; Rehana Kousar; Muhammad Bilal (Environmental Research, 2025)

Comparative study on effect of Pleurotus florida treated and untreated wheat straw on feed intake, digestibility, and growth rate in cattle calves - Muhammad Tahir Khan; Haq Aman Ullah; Ihtisham Ul Haq; Maria Munir; Syeda Maryam Hussain; Muhammad Mushtaq; Nazir Ahmad Khan (Tropical Animal Health and Production, 2025)

Reactive oxygen species production and signal transduction in response to stress triggered by Alternaria elicitors in Brassicaceae - Sana Munir; Ahmad N. Shahzad; Avanish Rai; Veselin Petrov; Tsanko Gechev; Sajid Shokat; Muhammad K. Qureshi (Plant Molecular Biology, 2025)

Identification of a biallelic MMUT variant (p.Thr230Arg) and its global perspective on clinical management - Sumreena Mansoor; Qamar Ali; Sabeen Abid Khan; Munir Iqbal Malik; Muhammad Imran; Raheel Qamar; Maleeha Azam (Molecular Biology Reports, 2025)

Sustainable Modeling and Optimization of Green-Synthesized ZnO Nanoparticles and Humic-Citric Amendments: Enhancing Growth, Nutrient Uptake, and Flowering of Solidago in Saline Soils - Khaled M.A. Ramadan; Hisham Mohamed; Muhammad Munir; Samah M. Youssef; Hossam S. El-Beltagi; Hani S. Saudy; Sallah A. Al Hashedi; Muhammad Naeem Sattar; Ahmed S. Abdelbaky; Ibrahim A. A. Mohamed; Mohamed M. El-Mogy; Wael M. Semida; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Biofunctional and ecotoxicological assessment of Rosa indica derived nitrogen-doped Carbon Dots: A new frontier for sustainable nanomaterials - Hubza Ruatt Khan; Humaira Yasmeen; Muhammad Asad Tahir; Asna Fatima Kiani; Iqra Munir; Unzish Qamar; Sara Janiad; Saher Mahmood (Biocatalysis and Agricultural Biotechnology, 2025)

Improvement in swell and consolidation behavior of sheard clay using glass powder and polypropylene fibers as additives - Syed Zishan Ashiq; Babar Naseem Khan Raja; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Muhammad Hassan (Innovative Infrastructure Solutions, 2025)

Reborn from fertilizer to fire safety: Development of effective gel flame retardants using recovered phosphorus from wastewater - Chenghui Yan; Bing Li; Lixia Qiu; Jingfu Chen; Jingsi Gao; Muhammad Tajammal Munir; Xiaofeng Wu; Wei Yu; Yuefei Huang (Journal of Environmental Chemical Engineering, 2025)

Systematic review of the microbiological status of farmed and processed Tenebrio molitor: Insights on foodborne pathogens in food and feed applications - Xin Yan; Lenaïg Brulé; Muhammad Tanveer Munir; Michel Federighi; Jean-Michel Cappelier; Vanessa Jury; Boris Misery; Géraldine Boué (Food Control, 2025)

Epigenetic horizons in aquaculture: unlocking sustainable fish production - Khalid Hussain; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Ebru Yilmaz; Abdulrahman Alasmari; Muhammad Munir; Muhammad Zubair-ul-Hassan Arsalan; Adan Naeem (Fish Physiology and Biochemistry, 2025)

Levilactobacillus brevis MW362790 and Pediococcus pentosaceus MT323062 Alleviate Cadmium-Induced Oxidative Stress and Hepato-renal Toxicity - Mamoona Hameed; Saman Javed; Najma Arshad; Zaman Gul; Maria Mushtaq; Aneela Munir; Kiran Shazadi; Muhammad Arshad; Saleha Noureen (Current Microbiology, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

Synergizing ZIF-67 activity with polyetherimide to achieve dendrite and shuttle-free lithium sulfur batteries - Waseem Raza; Andleeb Mehmood; Arshad Hussain; Karma M. Albalawi; Munir Ahmad; Muhammad Ahmed; Manal S. Ebaid; Muhammad Asim Mushtaq; Nadeem Raza; Huayu Huang; Lihong Ao; Dongqing Liu; et al. (Chemical Engineering Journal, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Suppression of common scab disease in potato via application of antagonistic Trichoderma harzianum and Bacillus subtilis - Ihtisham Ul Haq; Mamoona Munir; Saira Qadir; Mushtaq Ahmad; Ayesha Ikram; Muhammad Asif; Zahid Mukhtar; Fathia Mubeen; Muhammad Akhtar; Ijaz Ahmed Qureshi (Journal of Plant Diseases and Protection, 2025)

Transboundary river water quality assessment: a case study of Kabul River Basin, Pakistan - Kashif Hussain; Muhammad Shahid Iqbal; Sarfraz Munir; Hazrat Bilal (Environmental Science and Pollution Research, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Recent advances in synthesis and modulation of 2D heterostructures for sensing and detection applications - Rumaisa Tariq; Waseem Raza; Karma M. Albalawi; Arshad Hussain; Munir Ahmad; Muhammad Asim Mushtaq; Mohamed H. Helal; Ibrahim A. Shaaban; Shaukat Khan; Muhammad Sufyan Javed (Chemical Engineering Journal, 2025)

Exploring the potential of novel feedstock (Caesalpinia bonduc seeds) for circular biodiesel production using seed shell-derived green nanocatalysts - Roshan Amjad; Mushtaq Ahmad; Shazia Sultana; Mamoona Munir; Muhammad Ishtiaq Ali; Mohamed M. El-Toony; Nizomova Maksuda Usmankulovna; Burkhan Avutkhanov; Ahmad Mustafa (Biomass and Bioenergy, 2025)

Physiochemical and transcriptomics of exotic holstein friesian cattle in Pakistani subtropics - Masood Ur Rehman; Rajwali Khan; Syed Muhammad Suhail; Iqbal Munir; Khalid Mahmood; Amel Ayari Akari (Tropical Animal Health and Production, 2025)

An automatic approach for the classification of lumpy skin disease in cattle - Fakhre Alam; Asad Ullah; Mohammed A. Rohaim; Muhammad Munir; Aftab Hussain (Tropical Animal Health and Production, 2025)

Overexpression of StDREB30 Gene Enhances Salt Stress Tolerance in Transgenic Potato - Qurat- Ul Ain-Ali; Faiza Munir; Muhammad Faraz Bhatti; Rabia Amir; Alvina Gul (Potato Research, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Weissella confusa MW051433 Mitigates Hypercholesterolemia by Biliary Cholesterol Excretion: The In Vivo Evidence - Saman Javed; Zakia Latif; Ghulam Ayesha Javed; Aneela Munir; Maria Mushtaq; Mamoona Hameed; Muhammad Arshad; Najma Arshad (Current Microbiology, 2025)

Diagenetic and mineralogical impacts on clastic reservoir; A case study from the lower Indus Basin, Pakistan - Muhammad Nofal Munir; Mohammad Zafar; Muhsan Ehsan; Rujun Chen; Kamal Abdelrahman; Jar Ullah; Tassawar Hayat; Hamad Ur Rahim (Journal of Asian Earth Sciences, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Adaptive floristic diversity and ecological responses to environmental gradients in the saline soil ecosystem - Sehrish Sadia; Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Mubashrah Munir; Asma Jabeen; Samreen Aslam (Journal for Nature Conservation, 2025)

Enhancing Wheat Yield and Zinc Biofortification through Synergistic Action of Potent Zinc-Solubilizing Bacteria and Zinc Sulfate in Calcareous Soil - Murad Ali; Iftikhar Ahmed; Munir Hussain Zia; Saira Abbas; Tariq Sultan; Muhammad Sharif (Agricultural Research, 2025)

Microplastic contamination in commercial food and drink products and associated risk of potential human intake in Riyadh, Saudi Arabia - Munir Ahmad; Jahangir Ahmad; Muhammad Usama; Hamed Ahmed Al-Swadi; Mohammed Awad Mousa; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. F. Al-Farraj (Environmental Monitoring and Assessment, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Impacts of microplastic accumulation in aquatic environment: Physiological, eco-toxicological, immunological, and neurotoxic effects - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Muhammad Munir; Abdul Ghafoor; Ebru Yilmaz; Mohammed Ali Alshehri; Danish Riaz; Adan Naeem; Eman Naeem (Aquatic Toxicology, 2025)

Development of a genotype-matched Newcastle disease DNA vaccine candidate adjuvanted with IL-28b for the control of targeted velogenic strains of Newcastle disease virus in Africa - Charlie F. Amoia; Augustino A. Chengula; Jean N. Hakizimana; Philemon N. Wambura; Muhammad Munir; Gerald Misinzo; James Weger-Lucarelli (Veterinary Research Communications, 2025)
Newcastle disease virus (NDV) is an extremely contagious and deadly virus that affects numerous bird species, posing serious threats to poultry production on a global scale. In addition to implementing biosecurity practices in farming systems, vaccination remains the most effective means of controlling Newcastle disease (ND). However, while existing commercial vaccines provide some level of protection, the effectiveness of these vaccines can be questionable, particularly in field settings where the complexity of vaccination program implementation poses significant challenges, especially against virulent genotypes of NDV. A genotype-matched NDV DNA vaccine could potentially offer a more effective vaccination approach than currently available live attenuated vaccines. By being specifically tailored to match circulating strains, such a vaccine might improve efficacy and reduce the risk of vaccine failure due to genotype mismatch. To develop an alternative vaccine approach, two ND DNA vaccines were constructed in this study. Each vaccine developed in this study contains the fusion (F) and haemagglutinin-neuraminidase (HN) genes of a virulent NDV genotype VII isolate from Tanzania. Interferon lambda-3 (IFNλ3; IL-28b), which has demonstrated capacity to significantly enhance specific adaptive immune responses and decreased levels of inflammatory cytokines, as well as improved protective responses at a high viral challenge dose, was included in one of the developed vaccines. These plasmids were designated pTwist-F-HN-VII-IL28b and pTwist-F-HN-VII. The two plasmids differed in that pTwist-F-HN-VII-IL28b contained the cytokine adjuvant IL-28b. Transfection of cells and subsequent immunofluorescence assays indicated that both plasmids expressed high levels of NDV F-HN proteins. In vivo immunization demonstrated that chicks intramuscularly immunized with pTwist-F-HN-VII-IL28b exhibited significant immune responses compared to chicks immunized with pTwist-F-HN-VII or the commonly used LaSota vaccine (LaSota), which was used as a control. The protective efficacy of pTwist-F-HN-VII-IL28b was 80% after challenge with the highly virulent NDV strain ON148423, compared to 60% for chicks vaccinated using LaSota, and pTwist-F-HN-VII. The findings of this study indicate that IL-28b can be employed as a molecular adjuvant for NDV vaccines. This study represents a key milestone in Newcastle disease vaccine research, particularly in the development of a genotype-matched DNA vaccine candidate. Additionally, this study demonstrated that the combination of F, HN, and IL-28b elicits an efficacious immune response against virulent NDV strains.

Insight into insecticide resistance mechanism and eco-friendly approaches for the management of olive fruit fly, Bactrocera oleae Rossi: a review - Ansa Majeed; Muhammad Tariq Rasheed; Javairia Akram; Noreen Shahzadi; Mehvish Kousar; Imran Bodlah; Javaid Iqbal; Inzamam Ul Haq; Yasir Munir; Junaid Ali Siddiqui (Journal of Plant Diseases and Protection, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Phenotypic and Molecular Screening for Yellow Rust Resistance in Chinese Wheat Hybrids as Impacted by Selection - Zainab Iftikhar; Muhammad Arif; Aamir Iqbal; Iqbal Munir; Sheng Quan Zhang; Chang Ping Zhao; Sajid Ali (Journal of Crop Health, 2025)
Exploring the potential of novel sources of wheat material is immensely important to combat the ever-changing pathogen causing wheat rust disease, associated with huge losses worldwide. This study focused on assessing rust (YR) resistance in Chinese wheat hybrids, combining molecular markers and field testing over two years with estimation of the impact of selection. Out of 416 hybrids, 108 were selected based on disease scoring parameters, showing negative genetic advancement for rust severity and coefficient of infection. The maximum rust severity reached 100% for four hybrids during the year 2017–18 whereas 70% for three hybrids during the year 2018–19. The maximum coefficient of infection was observed for four hybrids which were 100% (2017–18), whereas 70% for three hybrids (2018–19). Molecular genotyping with a set of five yellow rust resistance genes linked markers revealed that the most frequent molecular markers was Yr18 / Lr34 (among the YR markers), present in 92 out of 108 hybrids. All the five Yr genes were present only in 18 hybrids. Yr18 was the most common resistance gene detected in 85% hybrids, while Yr17 was the least detected gene (57%). Notably, the average coefficient of infection (ACI) was not directly associated with the number of resistant genes. Considering the overall performance, the hybrid lines 17BH002, 17BH057, 17BH073, 17BH109, 17BH123, 17BH128, 17BH190, 18BH026 and 17BH155 had an overall low yellow rust severity and co-efficient of infection and could be considering promising lines for further utilization. Clustering based on rust resistance genes categorized hybrids into five main clusters for YR resistance genes, showing variability among these valuable genetic resources. The observed variability in this study can be utilized for future breeding programs focused on developing resistant wheat varieties.

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Emerging organic micropollutants as serious environmental problem: A comprehensive review - Anna Wołowicz; Hafiz Muhammad Shahzad Munir (Science of The Total Environment, 2025)

Development of sustainable high-performance desert sand concrete: Engineering and environmental impacts of compression casting - Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Yu-Fei Wu (Resources, Conservation and Recycling, 2025)

Remediation of textile wastewater by hybrid technique using ZIF-67 catalyzed ozonation coupled with electrocoagulation - Farhan Javed; Muhammad Fahad Tariq; Amir Ikhlaq; Hafiz Muhammad Shahzad Munir; Ali Altaee (Journal of Water Process Engineering, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.

Bioaugmentation of a novel bacterial consortium in cotton-planted soil for lambda-cyhalothrin degradation - Samina ANWAR; Anusha LIAQAT; Asma MUNIR; Muhammad F. ASHRAF; Samina IQBAL (Pedosphere, 2024)

Viola stocksii: A rich source of antioxidant and anti-inflammatory flavonoid glycosides with converged therapeutic potential against SARS-CoV-2 MPro, spike trimer, and surface glycoproteins - Roshan Zamir; Shanza Munir; Humaira Yasmeen Gondal; Muhammad Nisar; Sami A. Al-Hussain; Ahmed Abbaskhan; Zain M. Cheema; Magdi E.A. Zaki; M. Iqbal Choudhary (Food Bioscience, 2024)

Alteration of the gut microbial composition of critically endangered Malayan tigers (Panthera tigris jacksoni) in captivity during enrichment phase - Mohamad Khairulmunir; Millawati Gani; Abd Rahman Mohd-Ridwan; Kayal Vizi Karuppannan; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Molecular Biology Reports, 2024)

Biological role and regulation of circular RNA as an emerging biomarker and potential therapeutic target for cancer - Ayman Saleem; Muhammad Umer Khan; Tazeen Zahid; Iqra Khurram; Muhammad Usman Ghani; Inam Ullah; Rakhtasha Munir; Daniela Calina; Javad Sharifi-Rad (Molecular Biology Reports, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

Renewable wind energy resources in offshore low wind speeds regions near the equator: A review - Z. Nizamani; A.K. Muhammad; Montasir Osman Ahmed Ali; Mubarak Abdul Wahab; A. Nakayama; Mirza Munir Ahmed (Ocean Engineering, 2024)

Effect of the combination of polyvinyl chloride (PVC) and steel slag waste on the durability and mechanical properties of composite mortars - Md. Alhaz Uddin; Numan Wali; Muhammad Tariq Bashir; Muhammad Ali Sikandar; Fahad Alsharari; Fayez Alanazi; Md. Munir Hayet Khan; Talal O. Alshammari (Innovative Infrastructure Solutions, 2024)

Synthesis of green magnetic hybrid adsorbents and their application for reactive red methyl 4 BL dye removal - Sadaf Gillani; Ruba Munir; Khuram Ali; Muhammad Zeeshan Bashir; Umme Habibah Siddiqua; Saima Noreen (Clean Technologies and Environmental Policy, 2024)

Immunoinformatic-based drug design utilizing hesperetin to target CISD2 activation for liver aging in humans - Saad Ilyas Baig; Maria Naseer; Abdur-Rehman Munir; Yasir Ali; Muhammad Asif Razzaq (Biogerontology, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

Green hybrid coagulants for water treatment: An innovative approach using alum and bentonite clay combined with eco-friendly plant materials for batch and column adsorption - Sidra Saqib; Amna Muneer; Ruba Munir; Murtaza Sayed; Muhammad Waqas; Tayyiba Aliyam; Fazila Younas; Mohammad Abul Farah; Mohamed Farouk Elsadek; Saima Noreen (Environmental Research, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Comparative toxicity of insecticides to the haemocytes of honeybee, Apis mellifera (Hymenoptera: Apidae) under laboratory conditions - Rehana Bibi; Munir Ahmad; Junaid Ali Siddiqui; Muhammad Tariq Raseed; Waqar Islam (International Journal of Tropical Insect Science, 2024)

Phosphorus recovery and tetracycline Mitigation: The role of Bacillus cereus LB-9 in struvite biomineralization from wastewater - Yi Meng; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang; Wei Yu; Bing Li (Chemosphere, 2024)

Recent advances in the detection and quantification of manufactured nanoparticles (MNPs) in complex environmental and biological matrices - Qumber Abbas; Muhammad Zia-ur-Rehman; Habib Ullah; Mehar Ahmed Mujtaba Munir; Muhammad Ubaid Ali; Amjad Ali; Krzysztof Pikon; Balal Yousaf (Journal of Cleaner Production, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Struvite biomineralization as a promising solution to break the pollutant-resource paradox of phosphorus - Baorui Liang; Degui Gao; Muhammad Tajammal Munir; Wei Yu; Xiaofeng Wu; Yuefei Huang; Han Li; Brent Young; Shungui Zhou; Bing Li (Chemical Engineering Journal, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Enhancing productivity and profitability of quinoa through optimization of plant spacing and weeding regimes - Muhammad Kashif Hanif; Irfan Afzal; Muhammad Kashif Munir; Abdul Khaliq; Hafiz Naeem Asghar (Field Crops Research, 2024)

Recent advancements in polyurethane-based membranes for gas separation - Noureen Arshad; Syeda Rubab Batool; Sadia Razzaq; Mubeen Arshad; Abher Rasheed; Munir Ashraf; Yasir Nawab; Muhammad Anwaar Nazeer (Environmental Research, 2024)

Synthesis of polymeric ferrite composites (Ni-CoFe2O4/Chitosan, Zn-NiFe2O4/Starch, Co-NiZnFe2O4/Polyaniline, Ni doped CrZnFe2O4/Alginate, and Cr doped ZnCoFe2O4/PVA) for the removal of reactive golden yellow-160 dye from wastewater - Ghulam Mustafa; Ruba Munir; Bushra Sadia; Fazila Younas; Murtaza Sayed; Amna Muneer; Muhammad Fahad Sardar; Gadah Albasher; Saima Noreen (Journal of Environmental Chemical Engineering, 2024)

Spatial variation in iodine content with relation to soil physicochemical properties in lower Himalayan region - Jawad Ali; Muhammad Mohiuddin; Xinfeng Wang; Zahid Hussain; Muhammad Irshad; Munir Zia; Rashid Pervez; Mohammad K. Okla; Shakeel Ahmad (Environmental Research, 2024)

Construction and Utilization of Innovative Zeolite/Perovskite/Graphene Oxide, Zeolite/Chitosan/Graphene Oxide, and Zeolite/Biochar/Graphene Oxide Nanohybrid Composites for Adsorptive Remediation of Cationic Dye from Wastewater - Nageen Mushtaq; Ruba Munir; Muhammad Zia-ur-Rehman; Zia ul-Haq; Muhammad Zeeshan Bashir; Amna Muneer; Hina Ambreen; Saima Noreen (Water Conservation Science and Engineering, 2024)

Halloysite nanotubes in biomedical applications: Recent approaches and future trends - Seyyed Behnam Abdollahi Boraei; Fatemeh Eshghabadi; Roghayeh Hosseinpour; Yasser Zare; Muhammad Tajammal Munir; Kyong Yop Rhee (Applied Clay Science, 2024)

From scraps to purification: innovative use of food waste-derived hydrochar in eradicating pharmaceutical pollutants - Najam Ul Saqib; Muhammad Naqvi; Bing Li; Ajit K. Sarmah; Muhammad Tajammal Munir (Environmental Science and Pollution Research, 2024)

In-depth characterization of particulate matter in a highly polluted urban environment at the foothills of Himalaya–Karakorum Region - Bahadar Zeb; Khan Alam; Zhongwei Huang; Fatma Öztürk; Peng Wang; Lyudmila Mihaylova; Muhammad Fahim Khokhar; Said Munir (Environmental Science and Pollution Research, 2024)

Changes in human heat discomfort and its drivers in Bangladesh - Adila Tanim Ekra; Mohammed Magdy Hamed; Zulfiqar Ali; Mohd Khairul Idlan Bin Muhammad; Md Munir Hayet Khan; Mohammad Kamruzzaman; Shamsuddin Shahid (Urban Climate, 2024)

Influences of emerging drying technologies on rice quality - Naveed Mahmood; Yanhong Liu; Xu Zheng; Zeeshan Munir; R. Pandiselvam; Yue Zhang; Mansab Ali Saleemi; Harimana Yves; Muhammad Sufyan; Dengwen Lei (Food Research International, 2024)

Exploring zeolite-based composites in adsorption and photocatalysis for toxic wastewater treatment: Preparation, mechanisms, and future perspectives - Iqra Liaquat; Ruba Munir; Naseer Ahmed Abbasi; Bushra Sadia; Amna Muneer; Fazila Younas; Muhammad Fahad Sardar; Muhammad Zahid; Saima Noreen (Environmental Pollution, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Biochar imparted constructed wetlands (CWs) for enhanced biodegradation of organic and inorganic pollutants along with its limitation - Ruba Munir; Amna Muneer; Bushra Sadia; Fazila Younas; Muhammad Zahid; Muhammad Yaseen; Saima Noreen (Environmental Monitoring and Assessment, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

From field to table: Ensuring food safety by reducing pesticide residues in food - Salman Munir; Asad Azeem; Muhammad Sikandar Zaman; Muhammad Zia Ul Haq (Science of The Total Environment, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Biochemical and in silico structural characterization of a cold-active arginase from the psychrophilic yeast, Glaciozyma antarctica PI12 - Nik Yusnoraini Yusof; Doris Huai Xia Quay; Shazilah Kamaruddin; Mohd Anuar Jonet; Rosli Md Illias; Nor Muhammad Mahadi; Mohd Firdaus-Raih; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Simultaneous solar steam and electricity generation from biochar based photothermal membranes - Abdul Ghaffar; Muhammad Usman; Munir Ullah Khan; Muhammad Hassan (Journal of Cleaner Production, 2024)

Temporal profiling of physiological, histological, and transcriptomic dissection during auxin-induced adventitious root formation in tetraploid Robinia pseudoacacia micro-cuttings - Saleem Uddin; Muhammad Zeeshan Munir; Eduardo Larriba; José Manuel Pérez-Pérez; Sadia Gull; Tariq Pervaiz; Umer Mahmood; Zahid Mahmood; Yuhan Sun; Yun Li (Planta, 2024)

Genome-wide screening and evolutionary analysis of ZIP (ZRT–IRT like proteins) family in cowpea (Vigna unguiculata L.) - Arif Ullah; Zamarud Shah; Iqbal Munir; Hamza Iqbal; Muhammad Zulfiqar Ahmad; Warda Sultan; Afrasyab Khan (Genetic Resources and Crop Evolution, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Histotoxicity induced by copper oxide nanoparticles (CuO-NPs) on developing mice (Mus musculus) - Munir Ahmad; Muhammad Khalil Ahmad Khan; Naveed Ahmad; Munazza Parveen; Khurram Shahzad; Ali Hasan (Food and Chemical Toxicology, 2024)

Green loops and clean skies: Optimizing municipal solid waste management using data science for a circular economy - Muhammad Tajammal Munir; Bing Li; Muhammad Naqvi; Abdul-Sattar Nizami (Environmental Research, 2024)

Silica-embedded nutrient-doped biochar improves nutrient availability and safflower (Carthamus tinctorius L.) growth in cadmium- and lead-contaminated soil - Munir Ahmad; Hamed Ahmed Al-Swadi; Jahangir Ahmad; Muhammad Usama; Mohammed Awad Mousa; Nahrir M. A. Lubis; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. Al-Farraj (Journal of Soils and Sediments, 2024)

Inversion techniques for focal mechanism determination of small-magnitude earthquakes: a comparative study using the Burewala earthquake ($$M_w$$ $$\sim $$ 4) in Pakistan - Sadia Sabahat; Mohammad Tahir; Fatima Munir; Bilal Saif; Muhammad Tahir Iqbal; Javed Iqbal; Talat Iqbal (Journal of Seismology, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Influence of biochar produced from negative pressure-induced carbonization on transformation of potentially toxic metal(loid)s concerning plant physiological characteristics in industrially contaminated soil - Ayesha Imtiyaz Cheema; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muyuan Lu; Samina Irshad; Krzysztof Pikon; Mehr Ahmed Mujtaba Munir; Muhammad Saqib Rashid (Journal of Environmental Management, 2023)

Characterization, Source Apportionment and Health Risk Assessment of Trace Metals in Groundwater of Metropolitan Area in Lahore, Pakistan - Yasir Karim Khan; Muhammad Toqeer; Munir H. Shah (Exposure and Health, 2023)

Urbanization and its impacts on land surface temperature and sea surface temperature in a tourist region in Mexico from 1990 to 2020 - Sarahi Sandoval; Jonathan Gabriel Escobar-Flores; Muhammad Badar Munir (Remote Sensing Applications: Society and Environment, 2023)

Advancing sustainable phosphorus removal and recovery with Metal-Organic frameworks (MOFs) - Degui Gao; Haodong Ji; Ruili Li; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang; Bing Li (Chemical Engineering Journal, 2023)

Nanotechnologies for environmental remediation and their ecotoxicological impacts - Mahnoor Ejaz; Alvina Gul; Munir Ozturk; Ahmed Hafeez; Bengu Turkyilmaz Unal; Sami Ullah Jan; Muhammad Taimur Siddique (Environmental Monitoring and Assessment, 2023)

Therapeutic Potential of Selenium Nanoparticles on Letrozole-Induced Polycystic Ovarian Syndrome in Female Wistar Rats - Maisra Azhar Butt; Hafiz Muhammad Shafique; Mahjabeen Mustafa; Nurain Baig Moghul; Anum Munir; Urwah Shamas; Sobia Tabassum; Mubin Mustafa Kiyani (Biological Trace Element Research, 2023)

Scavenging microplastics and heavy metals from water using jujube waste-derived biochar in fixed-bed column trials - Munir Ahmad; Nahrir M.A. Lubis; Muhammad Usama; Jahangir Ahmad; Mohammad I. Al-Wabel; Hamed A. Al-Swadi; Muhammad Imran Rafique; Abdullah S.F. Al-Farraj (Environmental Pollution, 2023)

Enhancing thermal efficiency and durability of sintered clay bricks through incorporation of polymeric waste materials - Ertugrul Erdogmus; Mucahit Sutcu; Osman Gencel; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Pedro Munoz Velasco; Togay Ozbakkaloglu (Journal of Cleaner Production, 2023)

Revolutionizing municipal solid waste management (MSWM) with machine learning as a clean resource: Opportunities, challenges and solutions - Muhammad Tajammal Munir; Bing Li; Muhammad Naqvi (Fuel, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Heterologous expression of bacterial dehydrin gene in Arabidopsis thaliana promotes abiotic stress tolerance - Nadir Zaman Khan; Akhtar Ali; Waqar Ali; Muhammad Aasim; Tariq Khan; Zaryab Khan; Iqbal Munir (Physiology and Molecular Biology of Plants, 2023)

Interactions of Metal‐Based Engineered Nanoparticles with Plants: An Overview of the State of Current Knowledge, Research Progress, and Prospects - Abdul Wahab; Asma Munir; Muhammad Hamzah Saleem; Mukhtar Iderawumi AbdulRaheem; Humera Aziz; Manar Fawzi Bani Mfarrej; Gholamreza Abdi (Journal of Plant Growth Regulation, 2023)

Global phosphorus cycling: The impact of international commercial trading and the path towards sustainable phosphorus management - Sin Jin Ng; Bing Li; Zhengyang He; Jing-Cheng Han; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang (Resources Policy, 2023)

Food waste hydrochar: An alternate clean fuel for steel industry - Muhammad Tajammal Munir; Najam Ul Saqib; Bing Li; Muhammad Naqvi (Fuel, 2023)

New approach in evaluating mask filtration efficiency using low-cost PM2.5 sensor and mobile mannequin method - Martin Adrian; Irfan Dwi Aditya; Muhammad Miftahul Munir (Atmospheric Pollution Research, 2023)

Enhanced soluble expression of active recombinant human interleukin-29 using champion pET SUMO system - Ayesha Munir; Nadeem Ahmed; Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Kausar Malik (Biotechnology Letters, 2023)

Testing of Magnetic ZnO/MgFe2O4 Heterostructures for Photocatalytic Removal of Synthetic Dye Pollutants from Wastewater - Muhammad Shoaib; Muhammad Adnan Munir; Muhammad Yasin Naz; Ghulam Abbas; Muhammad Irfan; Saifur Rahman; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2023)

Hydrogen Peroxide Promotes Terminal Heat Stress Recovery in Wheat by Strengthening Leaf Physiological Functioning - Muhammad Sarwar; Muhammad Farrukh Saleem; Siraj Ahmed; Hamza Maqsood; Saddam Hussain; Muhammad Ashfaq Wahid; Muhammad Kashif Munir; Muhammad Zafar; Najeeb Ullah; Ali Khoddami (Journal of Plant Growth Regulation, 2023)

Health risk assessment and bioaccumulation of potentially toxic metals from water, soil, and forages near coal mines of district Chakwal, Punjab, Pakistan - Nida Zainab; Shehzad Mehmood; Amna Shafiq-ur-Rehman; Adeela Munir; Zafar Iqbal Tanveer; Zaib Un Nisa; Muhammad Imran; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2023)

Assessment of water quality, trace metal pollution, source apportionment and health risks in the groundwater of Chakwal, Pakistan - Maryam Batool; Muhammad Toqeer; Munir H. Shah (Environmental Geochemistry and Health, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

Green synthesis of iron oxide nanoparticles using Bombax malabaricum for antioxidant, antimicrobial and photocatalytic applications - Sunmbal Awais; Hira Munir; Jawayria Najeeb; Fozia Anjum; Khalida Naseem; Naghmana Kausar; Muhammad Shahid; Muhammad Irfan; Nayra Najeeb (Journal of Cleaner Production, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Fabrication of Nano-bentonite-Based Organo-minerals Composites of Biochar: Characterization and Application to Remove Arsenate from Contaminated Water - Jahangir Ahmad; Abdullah S. Al-Farraj; Munir Ahmad; Mohammad I. Al-Wabel; Muhammad Imran Rafique; Hamed Ahmed Al-Swadi (Water, Air, & Soil Pollution, 2023)

Superior leaf physiological performance contributes to sustaining the final yield of cotton (Gossypium hirsutum L.) genotypes under terminal heat stress - Muhammad Sarwar; Muhammad Farrukh Saleem; Najeeb Ullah; Asjad Ali; Brian Collins; Muhammad Shahid; Muhammad Kashif Munir; Sang-Min Chung; Manu Kumar (Physiology and Molecular Biology of Plants, 2023)

Mobility, bioaccessibility, pollution assessment and risk characterization of potentially toxic metals in the urban soil of Lahore, Pakistan - Yasir Karim Khan; Muhammad Toqeer; Munir H. Shah (Environmental Geochemistry and Health, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Efficient detoxification of textile wastewater by applying Chenopodium album nanoparticles and its application in simulated metal-bearing effluents removal - Neelma Munir; Rabia Tariq; Zainul Abideen; Maria Hasnain; Muhammad Iftikhar Hussain; Rukhama Haq (Environmental Science and Pollution Research, 2023)

Unveiling safflower yield, oil content, water use efficiency, and membrane stability under differential irrigation regimes - Muhammad Sajid; Hassan Munir; Abdul Khaliq; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

High efficient conversion of Cannabis sativa L. biomass into bioenergy by using green tungsten oxide nano-catalyst towards carbon neutrality - Tehreem Usman Abbasi; Mushtaq Ahmad; Maliha Asma; Rozina; Mamoona Munir; Muhammad Zafar; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari; Adel E.M. Yahya; Muhammad Mubashir; Lai Fatt Chuah; Awais Bokhari (Fuel, 2023)

Synthesis of Metal Hydroxyapatite Nanoparticles and Their Application, Behavior, and Mechanism in the Removal of Cationic Dye Red 3R from Aqueous Media - Ujala Shafqaat; Ruba Munir; Khuram Ali; Muhammad Ahsan; Muhammad Zeeshan Bashir; Saima Noreen (Water, Air, & Soil Pollution, 2023)

The dynamic change trends and internal driving factors of green development efficiency: robust evidence from resource-based Yellow River Basin cities - Li Yue; Huizhen Yan; Fayyaz Ahmad; Najia Saqib; Abbas Ali Chandio; Muhammad Munir Ahmad (Environmental Science and Pollution Research, 2023)

A novel EKC perspective: do agricultural production, energy transition, and urban agglomeration achieve ecological sustainability? - Muhammad Qaiser Shahzad Khan; Qingyou Yan; Rafael Alvarado; Munir Ahmad (Environmental Science and Pollution Research, 2023)

Elucidating molecular characterization of chlorpyrifos and profenofos degrading distinct bacterial strains for enhancing seed germination potential of Gossypium arboreum L - Najeeba Paree Paker; Shehzad Mehmood; Muhammad Tariq Javed; Christos A. Damalas; Fazal ur Rehman; Hassan Javed Chaudhary; Muhammad Zeshan Munir; Mahrukh Malik (Environmental Science and Pollution Research, 2023)

Assessing the potential of green CdO2 nano-catalyst for the synthesis of biodiesel using non-edible seed oil of Malabar Ebony - Sumera Arshad; Mushtaq Ahmad; Mamoona Munir; Shazia Sultana; Muhammad Zafar; Sumreen Dawood; Rozina; Ahmad M. Alghamdi; Saira Asif; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Fuel, 2023)

Towards developing resistance to chickpea chlorotic dwarf virus through CRISPR/Cas9-mediated gene editing using multiplexed gRNAs - Muniba Abid Munir Malik; Muhammad Saleem Haider; Ying Zhai; Muhammad Azmat Ullah Khan; Hanu R. Pappu (Journal of Plant Diseases and Protection, 2023)

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Efficient application of newly synthesized green Bi2O3 nanoparticles for sustainable biodiesel production via membrane reactor - Sawaira; Mabkhoot Alsaiari; Mushtaq Ahmad; Mamoona Munir; Muhammad Zafar; Shazia Sultana; Sumreen Dawood; Abdulaziz Ibrahim Almohana; Al-Marzouki Hassan M.H; Abdulrahman Faraj Alharbi; Zubair Ahmad (Chemosphere, 2023)

Cleaner production of biodiesel from novel non-edible seed oil (Carthamus lanatus L.) via highly reactive and recyclable green nano CoWO3@rGO composite in context of green energy adaptation - Mamoona Munir; Muhammad Saeed; Mushtaq Ahmad; Amir Waseem; Mustafa Alsaady; Saira Asif; Anas Ahmed; Mohd Shariq Khan; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Fuel, 2023)

Silica modified biochar mitigates the adverse effects of salt and drought stress and improves safflower (Carthamus tinctorius L.) growth - Munir Ahmad; Muhammad I. Rafique; Mutair A. Akanji; Mohammad I. Al-Wabel; Hamed A. Al-Swadi; Abdullah S. F. Al-Farraj (Journal of Soils and Sediments, 2023)

Consumption of Citrus mealybug, Planococcus citri by two predators, Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea (Stephen), under controlled conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq; Muneer Ahmad (International Journal of Tropical Insect Science, 2022)

Determinants of risk attitude and risk perception under changing climate among farmers in Punjab, Pakistan - Muhammad Farhan; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Sami Ullah; Saad Munir (Natural Hazards, 2022)

Variation in Vortex-Induced Vibration Phenomenon Due to Surface Roughness on Low- and High-Mass-Ratio Circular Cylinders: A Numerical Study - Muhammad Usman Anwar; Niaz Bahadur Khan; Muhammad Arshad; Adnan Munir; Muhammad Nasir Bashir; Mohammed Jameel; Muhammad Faisal Rehman; Sayed M. Eldin (Journal of Marine Science and Engineering, 2022)
Fluid–structure interaction has been widely studied in the last few decades due to its wide range of applications in engineering fields. This phenomenon plays an important design role, for example, in offshore risers, high slender buildings, chimney stacks and heat exchangers. The vortex shedding generated from a bluff body can induce high-amplitude oscillations, known as vortex-induced vibrations (VIVs). This study presents a numerical analysis to investigate the impact of surface roughness on VIV in the crossflow direction of a circular cylinder. The study also investigates the impact of surface roughness with variation in mass ratio from 2.4 to 11 at a high Reynolds number (Re) = 104 using Reynolds-averaged Navier–Stokes (RANS) equations. The study concludes that roughness on a cylinder results in a reduction in amplitude response. Furthermore, the lock-in region is narrower compared to that of a smooth cylinder, irrespective of the mass ratio. However, it is observed that the impact of surface roughness is more significant in high-mass-ratio cylinders where the lock-in region is more squeezed and shifted toward lower reduced velocities. Furthermore, the vortex mode beyond reduced velocities Ur = 5.84 and 7.52 was observed to be 2S for high and low mass ratios, respectively.

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Impact of Climate Change on Dryland Agricultural Systems: A Review of Current Status, Potentials, and Further Work Need - Mukhtar Ahmed; Rifat Hayat; Munir Ahmad; Mahmood ul-Hassan; Ahmed M. S. Kheir; Fayyaz ul-Hassan; Muhammad Habib ur-Rehman; Farid Asif Shaheen; Muhammad Ali Raza; Shakeel Ahmad (International Journal of Plant Production, 2022)

Production of a high molecular weight levan by Bacillus paralicheniformis, an industrially and agriculturally important isolate from the buffalo grass rhizosphere - Anam Nasir; Waqar Ahmad; Fazal Sattar; Iram Ashfaq; Stephen R. Lindemann; Ming-Hsu Chen; Wim Van den Ende; Ebru Toksoy Ӧner; Onur Kirtel; Shazia Khaliq; Muhammad A. Ghauri; Munir A. Anwar (Antonie van Leeuwenhoek, 2022)

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Development of Organically Complexed-Bioaugmented Boron-Coated DAP and Its Effect on Yield and Quality of Canola (Brassica napus L.) - Tayyaba Samreen; Muhammad Imran; Zahir Ahmad Zahir; Muhammad Zulqernain Nazir; Saima Noureen; Safdar Bashir; Sehrish Kanwal; Hassan Munir; Muhammad Aamer Maqsood (Journal of Plant Growth Regulation, 2022)

Pyroptosis in acute pancreatitis and its therapeutic regulation - Abdullah Al Mamun; Suzia Aktar Suchi; Md. Abdul Aziz; Muhammad Zaeem; Fahad Munir; Yanqing Wu; Jian Xiao (Apoptosis, 2022)

Distribution and Bioaccumulation of Essential and Toxic Metals in Tissues of Thaila (Catla catla) from a Natural Lake, Pakistan and Its Possible Health Impact on Consumers - Muhammad Saleem; Javed Iqbal; Zongbo Shi; Scott H. Garrett; Munir H. Shah (Journal of Marine Science and Engineering, 2022)
Although fish are often recommended as a component of a healthy diet, the environmental accumulation of heavy metals in many fish species has been of considerable concern for those weighing the nutritional health benefits against adverse toxic outcome of excess intake of toxic metals. This study aimed to determine the concentration of essential and toxic metals in the tissues of Catla catla in Mangla Lake and to assess the possible risk to the consumers. Fifty samples of Catla catla were collected from Mangla Lake, Mirpur, Azad Jammu and Kashmir, Pakistan and analyzed for eighteen metals including essential and trace metals. The measured range concentrations (µg/g, wet weight) in muscle tissues, in decreasing order, were: K (955–1632), Ca (550–2081), Na (449–896), Mg (129–312), Zn (61.2–215), Fe (11.6–26.8), Sr (2.60–9.27), Pb (1.72–7.81), Se (1.55–3.55), Co (0.12–4.08), Mn (1.04–4.33), Ni (0.69–3.06), Cu (0.88–2.78), Cr (0.45–1.88), As (0.67–1.58), Cd (0.28–0.56), Hg (0.17–0.57) and Li (0.12–0.38). The metal concentrations found in this study were comparatively higher than those reported in literature. A majority of the metals exhibited higher accumulation in gills compared with those in scales and muscles. Mean levels of Pb, As, Co, Mn, Cd, Cr and Zn in Catla catla muscle were found to be exceeding the international permissible limits for the safe human consumption. The condition factor (K), as an indicator of fish health status, indicated that Catla catla of Mangla Lake are in good health condition. The metal pollution index (MPI) of gills (27.9), scales (12.5) and muscle (7.57) indicated low contamination. Moreover, human health risk was evaluated using estimated weekly intake (EWI) and daily intake (EDI), target hazard quotient (THQ), hazard index (HI) and target cancer risk (TCR). Estimated weekly and daily intake values for As, Cd, Cr, Hg, Ni and Pb were higher than provisional permissible tolerable weekly intake and permissible tolerable daily intake while THQ for As, Cd, Cr, Hg, Pb, Se and Zn was higher than 1. The THQ for As, Hg and Pb was several folds higher than 1, indicative of lifetime non-carcinogenic health risks to the consumers. The hazard index indicated cumulative risk, which greatly increased with increasing fish consumption. Target cancer risk indicated that the people eating the Catla catla from Mangla Lake were exposed to As, Cd, Cr, Ni and Pb with a significant lifetime carcinogenic risk. In summary, consumption of Catla catla from this lake was found to be associated with an increased lifetime risk to the general health of the consumers.

Correction to: Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2022)

Proximate composition and spatio-temporal heterogeneity of phytochemicals in Agave sisalana Perrine (sisal) adapted in different agro-ecological zones of Punjab, Pakistan - Sobia Shahzad; Mumtaz Hussain; Hassan Munir; Muhammad Arfan (Environmental Science and Pollution Research, 2022)

Retesting the EKC hypothesis through transmission of the ARMEY curve model: an alternative composite model approach with theory and policy implications for NAFTA countries - Serdar Ongan; Cem Işık; Umit Bulut; Sahir Karakaya; Rafael Alvarado; Muhammad Irfan; Munir Ahmad; Abdul Rehman; Imran Hussain (Environmental Science and Pollution Research, 2022)

Genome-Wide Identification and Expression Profiling of Tomato Invertase Genes Indicate Their Response to Stress and Phytohormones - John Kojo Ahiakpa; Mahmoud Magdy; Benjamin Karikari; Shoaib Munir; Muhammad Ali Mumtaz; Safir Ahmad Tamim; Saira Mahmood; Genzhong Liu; Weifang Chen; Ying Wang; Yuyang Zhang (Journal of Plant Growth Regulation, 2022)

Pharmacological evaluation of anti-arthritic potential of terpinen-4-ol using in vitro and in vivo assays - Sania Aslam; Waqas Younis; Muhammad Nasir Hayat Malik; Shah Jahan; Alamgeer; Ambreen Malik Uttra; Muhammad Usman Munir; Muhammad Roman (Inflammopharmacology, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Teratological effects of titanium dioxide nanoparticles in mice embryo - Munir Ahmad; Muhammad Khalil Ahmad Khan; Khurram Shahzad; Naveed Ahmad; Munazza Parveen; Muhammad Saleem Khan (Environmental Science and Pollution Research, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Gums-based engineered bio-nanostructures for greening the 21st-century biotechnological settings - Muhammad Bilal; Hira Munir; Muhammad Imran Khan; Mohsin Khurshid; Tahir Rasheed; Komal Rizwan; Marcelo Franco; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2022)

Factors associated with cycle threshold values (Ct-values) of SARS-CoV2-rRT-PCR - Naila Shoaib; Naila Noureen; Arwa Faisal; Muhammad Zaheer; Muhammad Imran; Ali Ahsan; Rimsha Munir; Nousheen Zaidi (Molecular Biology Reports, 2022)

Mechanisms of gene regulation by histone degradation in adaptation of yeast: an overview of recent advances - Safir Ullah Khan; Munir Ullah Khan; Fadia Kalsoom; Muhammad Imran Khan; Shuang Gao; Ahsanullah Unar; Muhammad Zubair; Muhammad Bilal (Archives of Microbiology, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Molecular characterization and hematological analysis of Listeria monocytogenes infection in dairy cows in Punjab (Pakistan) - Muhammad Zubair Munir; Jawaria Ali Khan; Muhammad Ijaz; Fareeha Akhtar (Archives of Microbiology, 2022)

Can heat shock protein 70 (HSP70) serve as biomarkers in Antarctica for future ocean acidification, warming and salinity stress? - Nur Athirah Yusof; Makdi Masnoddin; Jennifer Charles; Ying Qing Thien; Farhan Nazaie Nasib; Clemente Michael Vui Ling Wong; Abdul Munir Abdul Murad; Nor Muhammad Mahadi; Izwan Bharudin (Polar Biology, 2022)
The Antarctic Peninsula is one of the fastest-warming places on Earth. Elevated sea water temperatures cause glacier and sea ice melting. When icebergs melt into the ocean, it “freshens” the saltwater around them, reducing its salinity. The oceans absorb excess anthropogenic carbon dioxide (CO 2 ) causing decline in ocean pH, a process known as ocean acidification. Many marine organisms are specifically affected by ocean warming, freshening and acidification. Due to the sensitivity of Antarctica to global warming, using biomarkers is the best way for scientists to predict more accurately future climate change and provide useful information or ecological risk assessments. The 70-kilodalton (kDa) heat shock protein (HSP70) chaperones have been used as biomarkers of stress in temperate and tropical environments. The induction of the HSP70 genes ( Hsp70 ) that alter intracellular proteins in living organisms is a signal triggered by environmental temperature changes. Induction of Hsp70 has been observed both in eukaryotes and in prokaryotes as response to environmental stressors including increased and decreased temperature, salinity, pH and the combined effects of changes in temperature, acidification and salinity stress. Generally, HSP70s play critical roles in numerous complex processes of metabolism; their synthesis can usually be increased or decreased during stressful conditions. However, there is a question as to whether HSP70s may serve as excellent biomarkers in the Antarctic considering the long residence time of Antarctic organisms in a cold polar environment which appears to have greatly modified the response of heat responding transcriptional systems. This review provides insight into the vital roles of HSP70 that make them ideal candidates as biomarkers for identifying resistance and resilience in response to abiotic stressors associated with climate change, which are the effects of ocean warming, freshening and acidification in Antarctic organisms.

The role of innovation investment and institutional quality on green total factor productivity: evidence from 46 countries along the “Belt and Road” - Wei Qiu; Jinwei Zhang; Haitao Wu; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2022)

Reinvestigating the Environmental Kuznets Curve (EKC) hypothesis by a composite model constructed on the Armey curve hypothesis with government spending for the US States - Cem Işık; Serdar Ongan; Umit Bulut; Sahir Karakaya; Muhammad Irfan; Rafael Alvarado; Munir Ahmad; Abdul Rehman (Environmental Science and Pollution Research, 2022)

Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives - Muhammad Ubaid Ali; Siyi Lin; Balal Yousaf; Qumber Abbas; Mehr Ahmed Mujtaba Munir; Audil Rashid; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2022)

Prevalence, epidemiology, seasonality, and phylogeny of Anaplasma marginale in blood samples of goats collected from Punjab, Pakistan - Muhammad Naveed Aziz; Muhammad Irfan; Asia Parveen; Muhammad Asif; Maryam Ijaz; Sadia Mumtaz; Sezayi Ozubek; Munir Aktas; Rana Khalid Iqbal; Furhan Iqbal (Tropical Animal Health and Production, 2022)

Isatin derivatives as broad-spectrum antiviral agents: the current landscape - Tilal Elsaman; Malik Suliman Mohamed; Eyman Mohamed Eltayib; Hatem A. Abdel-aziz; Abualgasim Elgaili Abdalla; Muhammad Usman Munir; Magdi Awadalla Mohamed (Medicinal Chemistry Research, 2022)

Production of bimodal molecular weight levan by a Lactobacillus reuteri isolate from fish gut - Waqar Ahmad; Anam Nasir; Fazal Sattar; Iram Ashfaq; Ming-Hsu Chen; Azam Hayat; Mujaddad ur Rehman; Sainan Zhao; Shazia Khaliq; Muhammad Afzal Ghauri; Munir Ahmad Anwar (Folia Microbiologica, 2022)

Correction to: Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2022)

Analysis of the mechanism of the impact of internet development on green economic growth: evidence from 269 prefecture cities in China - Jianlong Wang; Weilong Wang; Qiying Ran; Muhammad Irfan; Siyu Ren; Xiaodong Yang; Haitao Wu; Munir Ahmad (Environmental Science and Pollution Research, 2022)

Dendritic Cell–Targeted Therapies to Treat Neurological Disorders - Asim Hussain; Hamza Rafeeq; Nimra Munir; Zara Jabeen; Nadia Afsheen; Khalil ur Rehman; Muhammad Bilal; Hafiz M. N. Iqbal (Molecular Neurobiology, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Energy structure, digital economy, and carbon emissions: evidence from China - Yan Li; Xiaodong Yang; Qiying Ran; Haitao Wu; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2021)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Does temperature matter for COVID-19 transmissibility? Evidence across Pakistani provinces - Muhammad Irfan; Muhammad Ikram; Munir Ahmad; Haitao Wu; Yu Hao (Environmental Science and Pollution Research, 2021)

Evaluation of Contamination Status and Health Risk Assessment of Essential and Toxic Metals in Cyprinus carpio from Mangla Lake, Pakistan - Muhammad Saleem; Zongbo Shi; Munir H. Shah (Biological Trace Element Research, 2021)

Comparative efficacy of Ovaprim and hMG (menotropin) to induce breeding in African catfish (Clarias gariepinus) - Muhammad Wajahat Ameer; Farhat Jabeen; Muhammad Asad; Ghazala Kaukab; Amnah Bashir; Misha Rasheed; Hafsa Younis; Naveed Munir; Javaria Nawaz; Rida Zainab; Muhammad Akram (Fish Physiology and Biochemistry, 2021)

Investigating the myth of smokeless industry: environmental sustainability in the ASEAN countries and the role of service sector and renewable energy - Fayyaz Ahmad; Muhammad Umar Draz; Abbas Ali Chandio; Lijuan Su; Munir Ahmad; Muhammad Irfan (Environmental Science and Pollution Research, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Do economic openness and electricity consumption matter for environmental deterioration: silver bullet or a stake? - Ali Jan; Zhao Xin-gang; Munir Ahmad; Muhammad Irfan; Shahid Ali (Environmental Science and Pollution Research, 2021)

Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Kainat Abid; Sundas Bukhari; Muhammad Asif; Ayesha Sattar; Maryam Arshad; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Tropical Animal Health and Production, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Do inward foreign direct investment and economic development improve local environmental quality: aggregation bias puzzle - Munir Ahmad; Gul Jabeen; Muhammad Irfan; Cem Işık; Abdul Rehman (Environmental Science and Pollution Research, 2021)

Progress in nuclear energy with carbon pricing to achieve environmental sustainability agenda: on the edge of one’s seat - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Convergence analysis of the ecological footprint: theory and empirical evidence from the USMCA countries - Cem Işık; Munir Ahmad; Serdar Ongan; Dilek Ozdemir; Muhammad Irfan; Rafael Alvarado (Environmental Science and Pollution Research, 2021)

Another outlook to sector-level energy consumption in Pakistan from dominant energy sources and correlation with economic growth - Abdul Rehman; Hengyun Ma; Ilhan Ozturk; Munir Ahmad; Abdul Rauf; Muhammad Irfan (Environmental Science and Pollution Research, 2021)

Spatio‐temporal evaluation of gridded precipitation products for the high‐altitude Indus basin - Zakir Hussain Dahri; Fulco Ludwig; Eddy Moors; Shakil Ahmad; Bashir Ahmad; Muhammad Shoaib; Irfan Ali; Muhammad Shahid Iqbal; Muhammad Saleem Pomee; Abdul Ghafoor Mangrio; Muhammad Munir Ahmad; Pavel Kabat (International Journal of Climatology, 2021)
The high‐altitude Indus basin is one of the most complex and inadequately explored mountain terrains in the World, where reliable observations of precipitation are highly lacking. Therefore, spatially distributed precipitation products developed at global/regional scale are often used in several scientific disciplines. However, large uncertainties in precipitation estimates of such precipitation data sets often lead to suboptimal outcomes. In this study, performance of 27 widely used gridded precipitation products belonging to three different categories of gauge‐based, reanalysis and merged products is evaluated with respect to high‐quality reference climatologies of mean monthly precipitation. Widely used statistical measures and quantitative analysis techniques are used to analyse the spatial patterns and quantitative distribution of mean monthly, seasonal and annual precipitation at sub‐regional scale. Mean annual precipitation estimates of the gridded data sets are cross validated with the corresponding adjusted streamflows using Turc‐Budyko non‐dimensional analysis. Results reveal poor to moderately good performance of the gridded data sets. Marked differences in spatiotemporal and quantitative distribution of precipitation are found among the data sets. All data sets are consistent in their patterns showing negative or dry bias in wet areas and positive or wet bias in dry areas, although considerable differences in the magnitudes of the biases are noticed at sub‐regional scale. None of the data sets is equally good for all sub‐regions due to very high spatiotemporal variability in their performance at sub‐regional scale. Gauge‐based and merged products performed better in dry regions and during monsoon season, while reanalysis products provided better estimates in wet areas and during winter months. GPCC V8, ERA5 and MSWEP2.2 are found better than their counter‐grouped data sets. Overall, ERA5 is found most acceptable for all sub‐regions, particularly at higher‐altitudes, in wet areas and during winter months.

Effect of profenofos and citrus oil on Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea Stephens, key predators of citrus mealybug, Planococcus citri (Risso), under laboratory conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq (International Journal of Tropical Insect Science, 2021)

Correction to: Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

How do climatic change, cereal crops and livestock production interact with carbon emissions? Updated evidence from China - Abdul Rehman; Hengyun Ma; Munir Ahmad; Ilhan Ozturk; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2021)

Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles in Sargodha, Pakistan - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

The increases and decreases of the environment Kuznets curve (EKC) for 8 OECD countries - Cem Isik; Serdar Ongan; Dilek Ozdemir; Munir Ahmad; Muhammad Irfan; Rafael Alvarado; Ayşe Ongan (Environmental Science and Pollution Research, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

Physiological insights into sulfate and selenium interaction to improve drought tolerance in mung bean - Muhammad Aqib; Fahim Nawaz; Sadia Majeed; Abdul Ghaffar; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muhammad Naeem Tahir; Muhammad Aurangzaib; Hafiz Muhammad Rashad Javeed; Muhammad Habib-ur-Rahman; Muhammad Munir Usmani (Physiology and Molecular Biology of Plants, 2021)
The present study involved two pot experiments to investigate the response of mung bean to the individual or combined SO 4 2− and selenate application under drought stress. A marked increment in biomass and NPK accumulation was recorded in mung bean seedlings fertilized with various SO 4 2− sources, except for CuSO 4 . Compared to other SO 4 2− fertilizers, ZnSO 4 application resulted in the highest increase in growth attributes and shoot nutrient content. Further, the combined S and Se application (S + Se) significantly enhanced relative water content (16%), SPAD value (72%), photosynthetic rate (80%) and activities of catalase (79%), guaiacol peroxidase (53%) and superoxide dismutase (58%) in the leaves of water-stressed mung bean plants. Consequently, the grain yield of mung bean was markedly increased by 105% under water stress conditions. Furthermore, S + Se application considerably increased the concentrations of P (47%), K (75%), S (80%), Zn (160%), and Fe (15%) in mung bean seeds under drought stress conditions. These findings indicate that S + Se application potentially increases the nutritional quality of grain legumes by stimulating photosynthetic apparatus and antioxidative machinery under water deficit conditions. Our results could provide the basis for further experiments on cross-talk between S and Se regulatory pathways to improve the nutritional quality of food crops.

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

The role of information and communication technologies in mitigating carbon emissions: evidence from panel quantile regression - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Asymmetric investigation to track the effect of urbanization, energy utilization, fossil fuel energy and CO2 emission on economic efficiency in China: another outlook - Abdul Rehman; Hengyun Ma; Muhammad Zubair Chishti; Ilhan Ozturk; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2021)

Correction to: Potential reverse spillover of infectious bursal disease virus at the interface of commercial poultry and wild birds - Rania F. El Naggar; Mohammed A. Rohaim; Muhammad Munir (Virus Genes, 2021)
The original version of this article unfortunately contained an error in figure.

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Correction to: Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

A Report on Molecular Detection and Phylogenetic Evaluation of Anaplasma marginale in Ticks and Blood Samples Collected from Cattle in District Layyah in Punjab (Pakistan) - Sehrish Ashraf; Asia Parveen; Mian Muhammad Awais; Quratulane Gillani; Munir Aktas; Sezayi Ozubek; Furhan Iqbal (Current Microbiology, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

Potential reverse spillover of infectious bursal disease virus at the interface of commercial poultry and wild birds - Rania F. El Naggar; Mohammed A. Rohaim; Muhammad Munir (Virus Genes, 2020)
Recently, multiple spillover events between domesticated poultry and wild birds have been reported for several avian viruses. This phenomenon highlights the importance of the livestock-wildlife interface in the possible emergence of novel viruses. The aim of the current study was to investigate the potential spillover and epidemiological links of infectious bursal disease virus (IBDV) between wild birds and domestic poultry. To this end, twenty-eight cloacal swabs were collected from four species of free-living Egyptian wild birds (i.e. mallard duck, bean goose, white-fronted goose and black-billed magpie). Genetic and phylogenetic analysis of three positive isolates revealed that the IBDV/USC-1/2019 strain clustered with previously reported very virulent IBDV (vvIBDV) Egyptian isolates. Interestingly, two other wild bird-origin isolates (i.e. IBDV/USC-2/2019 and IBDV/USC-3/2019) grouped with a vaccine strain that is being used in commercial poultry. In conclusion, our results revealed the molecular detection of vaccine and vvIBDV-like strains in Egyptian wild birds and highlighted the potential role of wild birds in IBDV epidemiology in disease-endemic regions.

Correction to: A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Phenotypic characterisation and linkage mapping of domestication syndrome traits in yellow lupin (Lupinus luteus L.) - Muhammad Munir Iqbal; William Erskine; Jens D. Berger; Matthew N. Nelson (Theoretical and Applied Genetics, 2020)
The transformation of wild plants into domesticated crops usually modifies a common set of characters referred to as ‘domestication syndrome’ traits such as the loss of pod shattering/seed dehiscence, loss of seed dormancy, reduced anti-nutritional compounds and changes in growth habit, phenology, flower and seed colour. Understanding the genetic control of domestication syndrome traits facilitates the efficient transfer of useful traits from wild progenitors into crops through crossing and selection. Domesticated forms of yellow lupin ( Lupinus luteus L.) possess many domestication syndrome traits, while their genetic control remains a mystery. This study aimed to reveal the genetic control of yellow lupin domestication traits. This involved phenotypic characterisation of those traits, defining the genomic regions controlling domestication traits on a linkage map and performing a comparative genomic analysis of yellow lupin with its better-understood relatives, narrow-leafed lupin ( L. angustifolius L.) and white lupin ( L. albus L.). We phenotyped an F 9 recombinant inbred line (RIL) population of a wide cross between Wodjil (domesticated) × P28213 (wild). Vernalisation responsiveness, alkaloid content, flower and seed colour in yellow lupin were each found to be controlled by single loci on linkage groups YL-21, YL-06, YL-03 and YL-38, respectively. Aligning the genomes of yellow with narrow-leafed lupin and white lupin revealed well-conserved synteny between these sister species (76% and 71%, respectively). This genomic comparison revealed that one of the key domestication traits, vernalisation-responsive flowering, mapped to a region of conserved synteny with the vernalisation-responsive flowering time Ku locus of narrow-leafed lupin, which has previously been shown to be controlled by an FT homologue. In contrast, the loci controlling alkaloid content were each found at non-syntenic regions among the three species. This provides a first glimpse into the molecular control of flowering time in yellow lupin and demonstrates both the power and the limitation of synteny as a tool for gene discovery in lupins.

Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2020)

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

Does carbon dioxide, methane, nitrous oxide, and GHG emissions influence the agriculture? Evidence from China - Abdul Rehman; Hengyun Ma; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2020)

Study of Trace Metal Imbalances in the Scalp Hair of Stomach Cancer Patients with Different Types and Stages - Annum Afzal; Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Disparities in Trace Metal Levels in Hodgkin/Non-Hodgkin Lymphoma Patients in Comparison with Controls - Muhammad Abdul Qayyum; Munir Hussain Shah (Biological Trace Element Research, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Muhammad Asif; Asia Parveen; Sehrish Ashraf; Mureed Hussain; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Acta Parasitologica, 2020)

Revealing heterogeneous causal links among financial development, construction industry, energy use, and environmental quality across development levels - Munir Ahmad; Gul Jabeen; Muhammad Khizar Hayat; Rana Ejaz Ali Khan; Shoaib Qamar (Environmental Science and Pollution Research, 2020)

Spatiotemporal variability in spate irrigation systems in Khirthar National Range, Sindh, Pakistan (case study) - Abdul Ghani Soomro; Muhammad Munir Babar; Muhammad Arshad; Anila Memon; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

In situ immobilization of Cr and its availability to maize plants in tannery waste–contaminated soil: effects of biochar feedstock and pyrolysis temperature - Muhammad Imran Rafique; Adel R. A. Usman; Munir Ahmad; Abdelazeem Sallam; Mohammad I. Al-Wabel (Journal of Soils and Sediments, 2020)

Modeling heterogeneous dynamic interactions among energy investment, SO2 emissions and economic performance in regional China - Munir Ahmad; Zhen-Yu Zhao; Muhammad Irfan; Marie Claire Mukeshimana; Abdul Rehman; Gul Jabeen; Heng Li (Environmental Science and Pollution Research, 2020)

Role of cotton sticks biochar in immobilization of nickel under induced toxicity condition and growth indices of Trigonella corniculata L. - Uzma Younis; Subhan Danish; Saeed Ahmad Malik; Niaz Ahmed; Tariq Muhammad Munir; Muhammad Khalid Rasheed (Environmental Science and Pollution Research, 2020)

Application of water quality index, synthetic pollution index, and geospatial tools for the assessment of drinking water quality in the Indus Delta, Pakistan - Ghulam Shabir Solangi; Altaf Ali Siyal; Muhammad Munir Babar; Pirah Siyal (Environmental Monitoring and Assessment, 2019)

A comparative phylogenomic analysis of peste des petits ruminants virus isolated from wild and unusual hosts - Aziz-ul- Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Biology Reports, 2019)

A comparative genomic and evolutionary analysis of circulating strains of Avian avulavirus 1 in Pakistan - Aziz-ul Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Genetics and Genomics, 2019)

Emergence and genetic analysis of variant pathogenic 4/91 (serotype 793/B) infectious bronchitis virus in Egypt during 2019 - Mohammed A. Rohaim; Rania F. El Naggar; Mohamed M. Hamoud; Abdel-Hamid I. Bazid; Abdulrhman M. Gamal; Samah E. Laban; Mohammed A. Abdel-Sabour; Shimaa A. E. Nasr; Manal M. Zaki; Muhammad Z. Shabbir; Osama K. Zahran; Muhammad Munir (Virus Genes, 2019)

Impact of biochar with different organic materials on carbon fractions, aggregate size distribution, and associated polysaccharides and soil moisture retention in an arid soil - Munir Abbas; Shahzada Sohail Ijaz; Muhammad Ansar; Qaiser Hussain; Asma Hassan; Muhammad Akmal; Muhammad Tahir; Muhammad Iqbal; Kashif Bashir; Sana-ur-Rehman (Arabian Journal of Geosciences, 2019)

Feedstock-induced changes in composition and stability of biochar derived from different agricultural wastes - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Munir Ahmad; Muhammad Ashfaq (Arabian Journal of Geosciences, 2019)

A cross-sectional study of methicillin-resistant Staphylococcus aureus at the equine-human interface - Namra Waqar; Quratulain Amin; Tariq Munir; Muhammad Sohaib Ikram; Naveed Shahzad; Arkim Mirza; Arshad Ali; Muhammad Imran Arshad (Tropical Animal Health and Production, 2019)

Revealing long- and short-run empirical interactions among foreign direct investment, renewable power generation, and CO2 emissions in China - Munir Ahmad; Zhen-Yu Zhao; Abdul Rehman; Muhammad Shahzad; Heng Li (Environmental Science and Pollution Research, 2019)

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies - Iram Sharif; Saba Aleem; Jehanzeb Farooq; Muhammad Rizwan; Abia Younas; Ghulam Sarwar; Shahid Munir Chohan (Physiology and Molecular Biology of Plants, 2019)

Environmental and economic impacts of better cotton: a panel data analysis - Sundas Zulfiquar; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Samiullah; Saad Munir (Environmental Science and Pollution Research, 2019)

A systematic review on global pollution status of particulate matter-associated potential toxic elements and health perspectives in urban environment - Muhammad Ubaid Ali; Guijian Liu; Balal Yousaf; Habib Ullah; Qumber Abbas; Mehr Ahmad Mujtaba Munir (Environmental Geochemistry and Health, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Engineered biochar composites with zeolite, silica, and nano-zerovalent iron for the efficient scavenging of chlortetracycline from aqueous solutions - Munir Ahmad; Adel R. A. Usman; Muhammad Imran Rafique; Mohammad I. Al-Wabel (Environmental Science and Pollution Research, 2019)

Empirics on influencing mechanisms among energy, finance, trade, environment, and economic growth: a heterogeneous dynamic panel data analysis of China - Munir Ahmad; Zhen-Yu Zhao; Muhammad Irfan; Marie Claire Mukeshimana (Environmental Science and Pollution Research, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Is Malaysia’s banded langur, Presbytis femoralis femoralis, actually Presbytis neglectus neglectus? Taxonomic revision with new insights on the radiation history of the Presbytis species group in Southeast Asia - Muhammad Abu Bakar Abdul-Latiff; Hanisah Baharuddin; Pazil Abdul-Patah; Badrul Munir Md-Zain (Primates, 2019)

Biological characterization of wild-bird-origin avian avulavirus 1 and efficacy of currently applied vaccines against potential infection in commercial poultry - Rania F. El Naggar; Mohammed A. Rohaim; AbdelHamid H. Bazid; Kawkab A. Ahmed; Hussein A. Hussein; Muhammad Munir (Archives of Virology, 2018)

Vehicular emissions on main roads in Makkah, Saudi Arabia—a dispersion modelling study - Said Munir; Turki Muhammad Habeebullah (Arabian Journal of Geosciences, 2018)

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos) - Momena Habib; Tahir Yaqub; Jawad Nazir; Wasim Shehzad; Aziz-ul-Rahman; Tayyebah Sohail; Nadia Mukhtar; Arsalan Mehboob; Muhammad Munir; Muhammad Zubair Shabbir (Archives of Virology, 2018)

Identification of pedilanthus leaf curl virus and associated betasatellite infecting turnip in Pakistan - Samrah Munir; Muhammad Khurshid; Hira Kanwal; Mujahid Hussain; Muhammad N. Sattar; Irfan Ali; Atiq-ur Rehman; Zafar Iqbal (Journal of Plant Pathology, 2018)

Biochemical and structural characterization of a novel cold-active esterase-like protein from the psychrophilic yeast Glaciozyma antarctica - Noor Haza Fazlin Hashim; Nor Muhammad Mahadi; Rosli Md Illias; Shevin Rizal Feroz; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

Evolutionary insights into the fusion protein of Newcastle disease virus isolated from vaccinated chickens in 2016 in Egypt - Ahmed Orabi; Ashraf Hussein; Ayman A. Saleh; Mohammed Abu El-Magd; Muhammad Munir (Archives of Virology, 2017)

Wheat productivity responses in the rice-based system under different no-till techniques and nitrogen sources - Muhammad Hamid Rafiq; Riaz Ahmad; Abdul Jabbar; Hassan Munir; Muzzammil Hussain (Environmental Science and Pollution Research, 2017)

Distribution of root-knot nematode species and their virulence on vegetables in northern temperate agro-ecosystems of the Pakistani-administered territories of Azad Jammu and Kashmir - Muhammad Tariq-Khan; Anjum Munir; Tariq Mukhtar; Johannes Hallmann; Holger Heuer (Journal of Plant Diseases and Protection, 2017)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Bioavailability evaluation, uptake of heavy metals and potential health risks via dietary exposure in urban-industrial areas - Balal Yousaf; Guijian Liu; Ruwei Wang; Muhammad Imtiaz; Muhammad Zia-ur-Rehman; Mehr Ahmed Mujtaba Munir; Zhiyuan Niu (Environmental Science and Pollution Research, 2016)

Isolation and characterization of genotype XIII Newcastle disease virus from Emu in India - Vasudevan Gowthaman; Sambhu Dayal Singh; Kuldeep Dhama; Perumal Aurumugam Desingu; Asok Kumar; Yashpal Singh Malik; Muhammad Munir (VirusDisease, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Bisphenol A exposure and healing effects of Adiantum capillus-veneris L. plant extract (APE) in bisphenol A-induced reproductive toxicity in albino rats - Balal Yousaf; Amina; Guijian Liu; Ruwei Wang; Abdul Qadir; Muhammad Ubaid Ali; Qudsia Kanwal; Bushra Munir; Asmatullah; Zaigham Abbas (Environmental Science and Pollution Research, 2016)

Erratum to: Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Germin-like protein 2 gene promoter from rice is responsive to fungal pathogens in transgenic potato plants - Faiza Munir; Satomi Hayashi; Jacqueline Batley; Syed Muhammad Saqlan Naqvi; Tariq Mahmood (Functional & Integrative Genomics, 2016)

Isolation of buffalo poxvirus from clinical case and variations in the genetics of the B5R gene over fifty passages - Mohsan Ullah Goraya; Zafar ul Ahsan Qureshi; Muhammad Abbas; Muhammad Ashraf; Muhammad Munir (Virus Genes, 2015)

Evaluation of weather research and forecasting model for the assessment of wind resource over Gharo, Pakistan - Muhammad Amjad; Qudsia Zafar; Firdos Khan; Muhammad Munir Sheikh (International Journal of Climatology, 2015)
Weather research and forecasting (WRF) model is the state‐of‐the‐art mesoscale model that could be used as a guideline to effectively assess the wind resource of Gharo wind station lying in the coastal belt of Pakistan. The anemometer heights of 10 and 30 m for the year 2005 have been used to study the wind profile of the region for summer (June, July, August, September) and winter (December, January, February, March). The study uses an innovative approach for model comparisons, i.e. an eta‐half level is added in the model on 60 m height and is interpolated to 30 m height by using well known power law. This is done by studying the diurnal variation of wind shear for the whole year of 2005 in order to reduce maximum possible interpolation error. For both seasons, the error measures of mean bias error (MBE), mean absolute error (MAE) and root mean square error (RMSE) of 30 m interpolated data were found lower than 10 m height data with increased correlation ( r ). A bias correction methodology (best easy systematic estimator) was further applied over the model output showing a significant improvement toward MBE, MAE and RMSE reduction, i.e. up to 99%, 73% and 68% on 10 m height and 99%, 51% and 46% on 30 m height. Errors were reduced more for summer than winter. The selected bias correction methodology was thus found to be highly applicable for both model heights. The wind energy assessment of Gharo wind station from the corrected model simulation showed summer having more potential for wind energy than winter with an estimated energy of up to 1000 MWh.

Phylogenetic characterization and novelty of organic sulphur metabolizing genes of Rhodococcus spp. (Eu-32) - Nasrin Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Shaun Heaphy (Biotechnology Letters, 2015)

Comparative Study of Trace Elements in Blood, Scalp Hair and Nails of Prostate Cancer Patients in Relation to Healthy Donors - Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2014)

Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Polar Biology, 2014)

Comparative Assessment of Selected Metals in the Scalp Hair and Nails of Lung Cancer Patients and Controls - Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2014)

Genetic analysis of Newcastle disease virus from Punjab, Pakistan - Muhammad Zubair Shabbir; Muhammad Abbas; Tahir Yaqub; Nadia Mukhtar; Atta Subhani; Hasham Habib; Muhammad Umar Sohail; Muhammad Munir (Virus Genes, 2013)

Thermal stress responses in Antarctic yeast, Glaciozyma antarctica PI12, characterized by real-time quantitative PCR - Sook Yee Boo; Clemente Michael Vui Ling Wong; Kenneth Francis Rodrigues; Nazalan Najimudin; Abdul Munir Abdul Murad; Nor Muhammad Mahadi (Polar Biology, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

In vitro callogenesis and detection of somaclonal variations in Plantago ovata L. - Tariq Mahmood; Aysha Jameel; Bilal Haider Abbasi; Faiza Munir; Syed Muhammad Saqlan Naqvi (Journal of Crop Science and Biotechnology, 2012)

Sequencing and analysis of the complete genome of Newcastle disease virus isolated from a commercial poultry farm in 2010 - Muhammad Munir; Siamak Zohari; Muhammad Abbas; Mikael Berg (Archives of Virology, 2012)

Assessment of background levels of trace metals in water and soil from a remote region of Himalaya - Munir H. Shah; Javed Iqbal; Nazia Shaheen; Nadeem Khan; Muhammad Aziz Choudhary; Gulraiz Akhter (Environmental Monitoring and Assessment, 2012)

Erratum to: Nitrogen-efficient rice cultivars can reduce nitrate pollution - Khalid Rehman Hakeem; Altaf Ahmad; Muhammad Iqbal; Salih Gucel; Munir Ozturk (Environmental Science and Pollution Research, 2012)

Whole genome sequencing and characterization of a virulent Newcastle disease virus isolated from an outbreak in Sweden - Muhammad Munir; Anna-Malin Linde; Siamak Zohari; Karl Ståhl; Claudia Baule; Björn Engström; Lena H. M Renström; Mikael Berg (Virus Genes, 2011)

Nitrogen-efficient rice cultivars can reduce nitrate pollution - Khalid Rehman Hakeem; Altaf Ahmad; Muhammad Iqbal; Salih Gucel; Munir Ozturk (Environmental Science and Pollution Research, 2011)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Complete genome characterisation of a Newcastle disease virus isolated during an outbreak in Sweden in 1997 - Anna-Malin Linde; Muhammad Munir; Siamak Zohari; Karl Ståhl; Claudia Baule; Lena Renström; Mikael Berg (Virus Genes, 2010)

Aflatoxin B1 in chilies from the Punjab region, Pakistan - Shahzad Z. Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi; Munir A. Sheikh; Haq N. Bhatti (Mycotoxin Research, 2010)

Future change in the frequency of warm and cold spells over Pakistan simulated by the PRECIS regional climate model - Siraj ul Islam; Nadia Rehman; Muhammad Munir Sheikh (Climatic Change, 2009)

Expression and characterization of Trichoderma virens UKM-1 endochitinase in Escherichia coli - Nadiawati Alias; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nik Azmi Nik Mahmood; Rosli Md Illias (World Journal of Microbiology and Biotechnology, 2009)

Comparative efficacy of standard AGID and precipitinogen inhibition test with monoclonal antibodies based competitive ELISA for the serology of Peste des Petits Ruminants in sheep and goats - Muhammad Munir; Muhammad Siddique; Qurban Ali (Tropical Animal Health and Production, 2009)

Removal of Nickel onto Alkali Treated Rice Bran - Muhammad Nadeem Zafar; Imran Abbas; Raziya Nadeem; Munir Ahmad Sheikh; Muhammad Afzal Ghauri (Water, Air, & Soil Pollution, 2009)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)

Pathogenicity of bacterium, Xenorhabdus nematophila isolated from entomopathogenic nematode (Steinernema carpocapsae) and its secretion against Galleria mellonella larvae - Ali Nawaz Mahar; Muhammad Munir; Sami Elawad; Simon Richard Gowen; Nigel Graham Meckenzi Hague (Journal of Zhejiang University-SCIENCE B, 2005)

Technical communication: Determination of cuprous ions in bacterial leachates and for environmental monitoring - Munir A. Anwar; Mazhar Iqbal; Muhammad A. Qamar; Moazur Rehman; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2000)